1999
DOI: 10.1152/ajpcell.1999.277.6.c1210
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and functional characterization of KCC3, a new K-Cl cotransporter

Abstract: We isolated and characterized a novel K-Cl cotransporter, KCC3, from human placenta. The deduced protein contains 1,150 amino acids. KCC3 shares 75-76% identity at the amino acid level with human, pig, rat, and rabbit KCC1 and 67% identity with rat KCC2. KCC3 is 40 and 33% identical to two Caenorhabditis elegans K-Cl cotransporters and approximately 20% identical to other members of the cation-chloride cotransporter family (CCC), two Na-K-Cl cotransporters (NKCC1, NKCC2), and the Na-Cl cotransporter (NCC). Hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
105
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(110 citation statements)
references
References 35 publications
(56 reference statements)
4
105
0
1
Order By: Relevance
“…These transporters are involved in cell proliferation (Shen et al, 2001) and in the electro-neutral movement of ions across the plasma membrane, thus controlling ionic and osmotic homeostasis of various cell types. The gene SLC12A6 is located on chromosome 15q13-14 (Hiki et al, 1999;Mount et al, 1999;Race et al, 1999). Several groups have demonstrated that mutations in SLC12A6 are causative for the recessively inherited Andermann syndrome (ACCPN, OMIM %218000), a severe neurological disorder characterized by agenesis of the corpus callosum, peripheral neuropathy (Howard et al, 2002bUyanik et al, 2006) and psychoses (Filteau et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…These transporters are involved in cell proliferation (Shen et al, 2001) and in the electro-neutral movement of ions across the plasma membrane, thus controlling ionic and osmotic homeostasis of various cell types. The gene SLC12A6 is located on chromosome 15q13-14 (Hiki et al, 1999;Mount et al, 1999;Race et al, 1999). Several groups have demonstrated that mutations in SLC12A6 are causative for the recessively inherited Andermann syndrome (ACCPN, OMIM %218000), a severe neurological disorder characterized by agenesis of the corpus callosum, peripheral neuropathy (Howard et al, 2002bUyanik et al, 2006) and psychoses (Filteau et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Neuron-specific KCC2 is present in the retina and central nervous system, where it plays a crucial role in maintaining low intracellular Cl − and GABAergic synaptic inhibition Rivera et al, 1999;Vardi et al, 2000;Vu et al, 2000). KCC3 shares a 77% overall amino acid identity with human KCC1, and is expressed at highest levels in skeletal muscle, heart, kidney, brain, and lens (Chee et al, 2006;Hiki et al, 1999;Lee et al, 2003;Mount et al, 1999;Pearson et al, 2001;Race et al, 1999). Human KCC4 shares a 69% amino acid identity with KCC2, and is expressed in muscle, heart, kidney, brain, lung, and lens (Chee et al, 2006;Lee et al, 2003;Mercado et al, 2000;Mount et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…They are highly conserved across species. They mediate the uptake of structurally diverse organic acids and some neutral compounds in exchange for intracellular ␣-ketoglutarate (21)(22)(23). Their substrates include many endogenous and exogenous compounds, such as dicarboxylates (20), prostaglandins (24), cyclic nucleotides and urate (16,20,23), nonsteroidal anti-inflammatory drugs (25), diuretics (26), antibiotics (27), and antiviral agents (28).…”
mentioning
confidence: 99%